Early neonatal Glutaric aciduria type I hidden by perinatal asphyxia: a case report - Giacomo Biasucci; Nicola Morelli; Federica Natacci; Massimo Mastrangelo (Italian Journal of Pediatrics, 2018)
Abstract Background Perinatal asphyxia (PA) occurs in about 2 to 10 per 1000 live full-term births. Although neonatal epileptic seizures are observed in up to 60% of cases, PA may mimic or subtend other conditions. Hypoxia related brain injury is particularly relevant, as it may have permanent effects on neuropsychomotor development. Antepartum obstetric conditions, may, in turn, lead to hypoxic-ischemic damage to the fetus and the newborn, often underlying PA. Herein, a case of PA that hid and triggered signs and symptoms of Glutaric Aciduria type I (GA-I), is reported. Case presentation R.F. was born at term after prolonged labour, by induced vaginal delivery with the Kristeller manoeuvre. He presented with severe asphyxia and asystoly. Immediate cardiopulmonary resuscitation promptly restored cardiorespiratory parameters, allowing for early extubation 30 min after. During the following hours, severe axial muscle hypotonia with an increased tone of the limb extensor muscles became evident. The absence of crying and archaic reflexes persisted and there was an onset of generalized tonic or clonic seizure. First level metabolic and inflammatory markers were within the normal range. An inherited metabolic disease was then suspected, due to the persistent clinical signs of severe neurological damage without any detectable septic parameter. GA-I was assessed and specific treatment started without any clinical improvement, although ensuring adequate growth and metabolic control. Thereafter, the baby developed a severe encephalopathy with drug resistant epileptic seizures. The progression of the neurological damage and a CVC-related sepsis led him to exitus at 2 years. Conclusions To the best of our knowledge, this is the first case of early post-natal onset of GA-I reported in literature to date, in the absence of expanded newborn screening (NBS) programme. As expanded NBS programmes for inborn errors of metabolism have not yet been internationally adopted, we are of the opinion that such diseases may well be hidden by misleading signs and symptoms imputable to other more frequent harmful clinical conditions. Moreover, it would be advisable that neonatologists be trained to include GA-I in the differential diagnosis of neurological damage secondary to PA.